Academic Self Efficacy Pada Mahasiswa Yang Sambil Bekerja - Alya Sagita, Nabila; Saut H. Hutahaean, Erik; Fahrudin, Adi (CV RIFAINSTITUT, 2023)
going to college and working is nothing new among students. It is not easy to carry out multiple roles simultaneously because you have to divide your time so that the two can run in balance. This condition causes students to tend to lose motivation in pursuing their studies and doubt their own abilities, thus demonstrating the need for strong academic self-efficacy. This study aims to determine whether self-efficacy influences academic burnout. In this study, there were 203 respondents with a total of 24 items who participated and met the criteria for filling out the questionnaire. To prove the research hypothesis about Academic Self-Efficacy based on gender and major, based on the results of the reliability test using Cronbach alpha, the coefficient on Academic Self-Efficacy is 0.862.